Effectiveness of predicting in-hospital mortality in critically ill children by assessing blood lactate levels at admission - Bai, Zhenjiang (BioMed Central, 2014)
BACKGROUND: Hyperlactatemia upon admission is a documented risk factor for mortality in critically ill adult patients. However, the predictive significance of a single lactate measurement at admission for mortality in the general population of critically ill children remains uncertain. This study evaluated the predictive value of blood lactate levels at admission and determined the cut-off values for predicting in-hospital mortality in the critically ill pediatric population. METHODS: We enrolled 1109 critically ill children who were admitted to a pediatric intensive care unit between July 2008 and December 2010. Arterial blood samples were collected in the first 2 hours after admission, and the lactate levels were determined. The Pediatric Risk of Mortality III (PRISM III) scores were calculated during the first 24 hours after admission. RESULTS: Of the 1109 children admitted, 115 (10.4%) died in the hospital. The median (interquartile range) blood lactate level in critically ill children was 3.2 mmol/l (2.2-4.8). Among the children, 859 (77.5%) had a lactate concentration >2.0 mmol/l. The blood lactate level upon admission was significantly associated with mortality (odds ratio [OR] = 1.38; 95% confidence interval [CI], 1.30-1.46; p <0.001), even after adjustment for age, gender, and illness severity assessed by PRISM III (OR = 1.27; p <0.001). Multivariate regression analysis showed that a high blood lactate level (OR = 1.17; 95% CI, 1.07-1.29; p = 0.001), a high PRISM III score (OR = 1.15; 95% CI, 1.11-1.20; p <0.001), and a low serum albumin (OR =0.92; 95% CI, 0.88-0.96; p <0.001) were independent risk factors for mortality in critically ill children. Blood lactate achieved an area under-the-receiver-operating-characteristic curve (AUC) of 0.79 (p <0.001) for predicting mortality that was similar to that of PRISM III (AUC = 0.82; p <0.001). The p-value for a comparison of both AUCs was 0.318. Blood lactate displayed a sensitivity of 61% and a specificity of 86% in predicting mortality at the optimal cut-off value of 5.55 mmol/l, and the positive and negative likelihood ratios were 4.5 and 0.45, respectively. CONCLUSIONS: A high blood lactate level at admission is independently associated with and predictive of in-hospital mortality in the general population of critically ill children.